PENGARUH MEDIA KOMUNIKASI DAN KEAKRABAN DENGAN KLIEN TERHADAP KEYAKINAN AUDITOR DALAM PENDETEKSIAN KECURANGAN - Widyatama, Widyatama; Kiswara, Endang (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the effect of media communication and familiarity with clients against the auditor's confidence in detection of fraud. This study is a replication of a study conducted by Cefaratti and Barkhi (2013) in the United States with differences in location, object, sampling and analytical methods.The research samples were 57 which were obtained from the auditors worked who in Public Accounting Firm (KAP). The data processed in this study are primary data and sample selection methods using simple random sampling system. By using t-test, this study are expected to measure the effect of communication media, familiarity with the client, and the impression received by the auditor of the client in detecting fraud.Research proves that face to face meetings give greater confidence to the auditor in detecting fraud. Familiarity with client affect auditors’ confidence in the detection of fraud and the information provided from the old client is trusted truth by auditors. In addition, the auditors feel the possibility of fraudulent information submitted by the client when the client gives a negative impression